Two new species of the millipede family Blaniulidae (Diplopoda, Julida) from caves in central and southeastern Europe - Antić, Dragan Ž.; Mock, Andrej; Enghoff, Henrik (Zootaxa, 2015)
Two new species, one each of the previously monotypic genera Cibiniulus Verhoeff, 1927, and Thassoblaniulus Mauriès, 1985, are described from caves in Slovakia and Albania, respectively: C. slovacus Antić, Mock & Enghoff, sp. n. and T. radjai Antić & Enghoff sp. n. Brief discussions on relationships with congeners and on the taxonomic position of the genera Cibiniulus and Thassoblaniulus within Blaniulidae are presented, as well as a distribution map for both genera.